Direct observation of antiferromagnetic parity violation in the electronic structure of Mn2Au. (19th October 2022) - Fedchenko, O; Šmejkal, L; Kallmayer, M; Lytvynenko, Ya; Medjanik, K; Babenkov, S; Vasilyev, D; Kläui, M; Demsar, J; Schönhense, G; Jourdan, M; Sinova, J; et al.
Abstract: Using momentum microscopy with sub- µ m spatial resolution, allowing momentum resolved photoemission on individual antiferromagnetic domains, we observe an asymmetry in the electronic band structure, E ( k ) ≠ E ( − k ), in Mn2 Au. This broken band structure parity originates from the combined time and parity symmetry, P T, of the antiferromagnetic order of the Mn moments, in connection with spin–orbit coupling. The spin–orbit interaction couples the broken parity to the Néel order parameter direction. We demonstrate a novel tool to image the Néel vector direction, N, by combining spatially resolved momentum microscopy with ab-initio calculations that correlate the broken parity with the vector N .